Damping of Low-Frequency Electrostatic Waves in Dusty Plasmas due to Continuous Size Spectrum of Dust Grains - Bliokh, P. V.; Yaroshenko, V. V. (Видавничий дім «Академперіодика», 2012)
Затухание низкочастотных электростатических волн в пылевой плазме с непрерывным спектром размеров пылинок